An iterative algebraic dynamic condensation method and its performance. (1st April 2017) - Boo, Seung-Hwan; Lee, Phill-Seung
Highlights: An iterative algebraic dynamic condensation method is newly developed. The iterative formulation of the reduced model is simply expressed at a submatrix level. Numerical examples demonstrate its excellent accuracy and computational efficiency. Abstract: A novel iterative reduced-order modeling method is proposed, which is based on the recently developed algebraic dynamic condensation method. The algebraic substructuring technique is employed to improve the reduction efficiency, and the initial reduced model is calculated using the substructural stiffness condensation and the interface boundary reduction procedures. Then, the initial reduced model is iteratively updated using the iterative substructural inertial effect condensation procedure until the solutions converge. The iterative formulation of the reduced model is represented simply with small submatrix operations to avoid huge computational cost induced by the iterative procedure resulting from the very large global transformation matrix. To verify the performance of the proposed method, we consider several large structural problems, and compare the numerical results to those of the iterated improved reduced system (IIRS) method, a widely used reduced-order modeling method.